2013
DOI: 10.1016/j.tca.2013.07.021
|View full text |Cite
|
Sign up to set email alerts
|

Kinetic modeling of low temperature oxidation of copper nanoparticles by O2

Abstract: International audienceThe mechanism and kinetics of copper nanoparticles oxidation at low temperature were investigated using thermogravimetry (TGA), differential scanning calorimetry (DSC), X-Ray diffraction (XRD) and transmission electron microscopy (TEM). Isothermal and isobaric studies of the oxidation reaction were carried out at various temperatures. It was found that working under an oxygen partial pressure of 1kPa in the temperature range 125 -145°C leads to reaction where nucleation of the oxide phase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(25 citation statements)
references
References 23 publications
4
21
0
Order By: Relevance
“…Subsequently, we gently oxidized three samples at 150°C in 1% O 2 in Ar carrier gas at atmospheric pressure for 30, 45 or 60 minutes, respectively. At these conditions, predominantly Cu 2 O is formed, while the growth of CuO is suppressed, 4,5,17,18,26 as we also have confirmed by XPS analysis in a previous study carried out at these conditions. 19 Simultaneous recording of the dark-field scattering response of a representative single Cu nanoparticle on each sample yields the temporal evolution of the recorded single particle spectra summarized in Fig.…”
Section: Resultssupporting
confidence: 86%
See 1 more Smart Citation
“…Subsequently, we gently oxidized three samples at 150°C in 1% O 2 in Ar carrier gas at atmospheric pressure for 30, 45 or 60 minutes, respectively. At these conditions, predominantly Cu 2 O is formed, while the growth of CuO is suppressed, 4,5,17,18,26 as we also have confirmed by XPS analysis in a previous study carried out at these conditions. 19 Simultaneous recording of the dark-field scattering response of a representative single Cu nanoparticle on each sample yields the temporal evolution of the recorded single particle spectra summarized in Fig.…”
Section: Resultssupporting
confidence: 86%
“…Among non-invasive in situ experimental techniques used to study metal nanoparticle oxidation, [15][16][17][18] visible light optical spectroscopy based on localized surface plasmon resonance (LSPR) is attractive because of its remote readout compatible with ambient pressures and elevated temperatures, and it has proven to be very useful in studies of the oxidation of Cu nanoparticles and the NKE. 4,5,19 However, to date such studies have been carried out on large ensembles of Cu nanoparticles (with one exception that did not focus on the oxidation process as such 20 ), which makes direct correlations between particle nanostructure, defects and oxidation mechanism difficult.…”
Section: Introductionmentioning
confidence: 99%
“…107 Several examples of the physico-geometrical consecutive process were analyzed kinetically using the principles from the nucleation and anisotropic growth models. [108][109][110][111] The integral kinetic behavior, which was characterized by a sigmoidal mass-loss curve under isothermal conditions, is superficially similar to those obtained for the reactions comprising the bulk nucleation and growth of nuclei, as formalized by the Johnson-Mehl-Avrami (JMA) model, [112][113][114][115] and the homogeneous-like autocatalytic model. 50,86,87 For the kinetic analysis conducted under isothermal conditions, reactions regulated by JMA and autocatalytic models could be treated as the pseudo-single-step reaction described by one rate constant;…”
Section: Kinetic Modeling Of the Consecutive Ip-sr-pbr Under Various supporting
confidence: 63%
“…However, a thin Cu 2 O shell may develop at the surface layer of the particles upon exposure to air, while the core of the particles remain stable as Cu(0). Mansour et al also observed the formation of a Cu 2 O shell around chemically synthesized Cu(0) nanoparticles under an oxygen atmosphere …”
Section: Resultsmentioning
confidence: 95%